Mechanical and Finite Element Analysis of a Tree Microstructural Model Derived from Softwood Annual Rings - Yasin Furkan Gorgulu; Murat Aydin (BioResources)
A Scotch pine wood annual ring (AR) structure was modeled using AutoCAD and SolidWorks software. The same AR was separately modeled to create earlywood (EW), transition wood (TW), and latewood (LW). All 3D models were additively manufactured using Hyper PLA material and Creality 3D printer. Compression tests were performed to obtain load-deformation curves. The maximum force, compression strength (CS), and deformation at 500N load were determined. The EW presented the highest deformation while LW presented the highest CS. The TW and AR displayed intermediate behaviors. Finite Element Modeling and Analysis (FEM&A) was performed to compare with the experimental results. The numerical results presented considerable high deviations from the experiment. Around 78.7%, 41.7%, 89.3%, and 52% differences were observed for AR, EW, TW, and LW, respectively. Therefore, the capability of the model for prediction of mechanical behavior was not found to be successful. The essential reason for these discrepancies is the contrast between the orthotropic nature of wood and partially anisotropic nature of 3D printed models even if the filament is isotropic material. However, it should be taken into consideration that such high differences are not abnormal for the wood material even if the tested samples belong to the same log because of the variations in the material due to sampling details such as cutting location, orientation, etc. Furthermore, when considering the 3D printing parameters such as infill density, printing orientation, layer height, etc., the FEM&A results can be considered partially successful, although the differences were high.